The Impact of Self-Reported Alcohol, Tobacco, and Recreational Drug Use during Pregnancy on Adverse Pregnancy Outcomes in First-Time Mothers - Daggy, Joanne K.; Silver, Robert M.; Guise, David; Haas, David M. (American Journal of Perinatology, 2022)
Objective The objective of this study was to derive profiles of alcohol, tobacco, and recreational drug use during pregnancy for first-time mothers with latent class growth analysis (LCGA) and determine the association of these classes with the risk of adverse pregnancy outcomes (APO).Study Design A secondary analysis of a prospective cohort of Nulliparous Outcomes in Pregnancy: Monitoring Mothers-to-Be was conducted in eight medical centers across the United States from September 30, 2010, to September 23, 2013. Self-reported use of any alcohol, tobacco, or recreational drugs in the 1 month prior to the visit was assessed at up to four visits throughout pregnancy, and APOs included a composite of preterm birth, hypertensive disorder of pregnancy (HDP), small for gestational age (SGA) infant, or stillbirth, and each adverse outcome separately.Results Four latent classes were identified from the LCGA for 10,031 nulliparous pregnant women that were on average 26.9 years old (standard deviation [SD] = 5.7) and mostly non-Hispanic White (59.7%). Classes included consistent tobacco users (N = 517, 5.2%), nonusers (N = 8,945, 89.2%), alcohol users (N = 500, 5.0%), and a combination of alcohol/tobacco/drug users (N = 69, 0.7%). Logistic regression demonstrated that the class of tobacco users was more likely to have an APO (odds ratio [OR] = 1.48, 95% confidence interval [CI] = 1.22–1.81), preterm birth (OR = 1.53, 95% CI = 1.15–2.02), and SGA (OR = 1.79, 95% CI = 1.36–2.35) relative to the class of nonusers. The class of alcohol users was more likely to have HDP (OR = 1.37, 95% CI = 1.11–1.70) and less likely to have preterm birth (OR = 0.59, 95% CI = 0.38–0.90) and SGA (OR = 0.61, 95% CI = 0.40–0.93) compared to nonusers.Conclusion Trajectories of substance use are associated with APOs; thus, interventions to mitigate the use when encountered early in pregnancy are warranted.Key Points
Keywords: substance use; latent class growth analysis; adverse pregnancy outcomes; preterm birth; hypertensive disorder of pregnancy; small for gestational age infant; stillbirth